2022
DOI: 10.1002/lary.30129
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Disparities in the Federal Drug Approval Process for Allergic Rhinitis Medications

Abstract: Objective: Demographic minorities are underrepresented in clinical trials. For the approval of new drug applications (NDAs), the Food and Drug Administration (FDA) has asserted that clinical trial enrollment should represent the demographics of patients likely to receive the trial drug. The aim of this study is to assess the demographics of clinical trials included in NDAs and biologics license applications (BLAs) approved by the FDA since 1990 for allergic rhinitis (AR), a condition whose demographic prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Allergic rhinitis (AR) is a chronic inflammatory disease of the nasal mucosa, which is caused by the release of immunoglobulin E (IgE)-mediated mediators (mainly histamine) after allergic individuals are exposed to allergens, and a variety of immune active cells and cell factors are involved [ 1 , 2 ]. In the USA, the prevalence of physician-diagnosed allergic rhinitis is about 15%, and patients self-report abnormal nasal symptoms up to 30% [ 3 , 4 ]. A Danish study spanning three decades reported that the prevalence of allergic rhinitis in the Danish adult population in the last three decades increased from 16% in 1990–1991 to 29% in 2012–2015, and the prevalence of allergic rhinitis is likely to continue to increase in this century [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Allergic rhinitis (AR) is a chronic inflammatory disease of the nasal mucosa, which is caused by the release of immunoglobulin E (IgE)-mediated mediators (mainly histamine) after allergic individuals are exposed to allergens, and a variety of immune active cells and cell factors are involved [ 1 , 2 ]. In the USA, the prevalence of physician-diagnosed allergic rhinitis is about 15%, and patients self-report abnormal nasal symptoms up to 30% [ 3 , 4 ]. A Danish study spanning three decades reported that the prevalence of allergic rhinitis in the Danish adult population in the last three decades increased from 16% in 1990–1991 to 29% in 2012–2015, and the prevalence of allergic rhinitis is likely to continue to increase in this century [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of prospective chronic rhinosinusitis (CRS) studies in the United States, encompassing over 12,000 patients, demonstrated that every demographic and ethnic minority was significantly underrepresented relative to its portion of the population (and probably relative to its share of CRS patients) 5 . Separate analyses of prospective clinical trials studying CRS and rhinitis through the National Institute of Health and the US Food and Drug Administration have also found that women and minorities are routinely underrepresented 6–8 . It is not hard to imagine a scenario where insurance companies utilize input from these biased data sets to create an algorithm to determine risk of disease progression, for example, and disproportionately deny sinus surgery coverage for women or minorities based on a skewed interpretation of responses to nonsurgical therapy.…”
mentioning
confidence: 99%
“…5 Separate analyses of prospective clinical trials studying CRS and rhinitis through the National Institute of Health and the US Food and Drug Administration have also found that women and minorities are routinely underrepresented. [6][7][8] It is not hard to imagine a scenario where insurance companies utilize input from these biased data sets to create an algorithm to determine risk of disease progression, for example, and disproportionately deny sinus surgery coverage for women or minorities based on a skewed interpretation of responses to nonsurgical therapy.…”
mentioning
confidence: 99%